Kaunas Tatar Community and Organization in 1918–1940: Structure and Work - Aleksandravičiūtė, Ina (Vilnius University Open Series, 2024)
After World War I Tatars in Lithuania had to reorganize and institutionalize their parishes. Though Kaunas Tatars didn’t accomplish much in spheres of culture and education, they managed to build a new mosque in Kaunas this way leaving their mark. The main goal of Kaunas Tatar community was creating religious central institution. In 1925 in Vilnius polish Tatar community established institution of Mufti. Kaunas Tatars tried to establish similar organizations thorough all interwar period. Sadly, the conflicts between Muslim parishes in Lithuania constantly stopped this process. Kaunas Tatar Association tried to become dominating institution in Lithuanian Muslim community. This initiative was supported by Lithuanian Government but Tatars of Raižiai and Vinkšnupiai parishes wanted to function independently.
Keywords: tatars; muslims; Kaunas Tatar Association; interwar; centralization; mosque; mečetė